2019
DOI: 10.1186/s12934-019-1238-2
|View full text |Cite
|
Sign up to set email alerts
|

Redirecting photosynthetic electron flux in the cyanobacterium Synechocystis sp. PCC 6803 by the deletion of flavodiiron protein Flv3

Abstract: BackgroundOxygen-evolving photoautotrophic organisms, like cyanobacteria, protect their photosynthetic machinery by a number of regulatory mechanisms, including alternative electron transfer pathways. Despite the importance in modulating the electron flux distribution between the photosystems, alternative electron transfer routes may compete with the solar-driven production of CO2-derived target chemicals in biotechnological systems under development. This work focused on engineered cyanobacterial Synechocysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 29 publications
(60 reference statements)
3
56
1
Order By: Relevance
“…Computational 40,41 and experimental 42,43 studies have shown that efficient production of some biochemicals would require lowering the ATP/NADPH ratio in the cyanobacteria cell. The was shown to lower cellular ATP/NADPH ratio in Synechocystis 43 . Finally, the CCA-tRNA nucleotidyltransferase pcnB, essential for tRNA maturation and thus protein synthesis, was also enriched.…”
Section: Resultsmentioning
confidence: 99%
“…Computational 40,41 and experimental 42,43 studies have shown that efficient production of some biochemicals would require lowering the ATP/NADPH ratio in the cyanobacteria cell. The was shown to lower cellular ATP/NADPH ratio in Synechocystis 43 . Finally, the CCA-tRNA nucleotidyltransferase pcnB, essential for tRNA maturation and thus protein synthesis, was also enriched.…”
Section: Resultsmentioning
confidence: 99%
“…One example for such a mechanism is the flavodiiron protein Flv3, which serves as a sink for excess electrons from the photosynthetic light reaction, by converting O 2 to H 2 O. A recent publication showed indeed increased PHB synthesis in a Flv3 deficient strain [33]. If PHB is indeed serving as an intracellular electron sink, its absence might be compensated by a higher activity of Flv3.…”
Section: Physiological Function Of Phbmentioning
confidence: 99%
“…It can be assumed that the correct regulation of the ATP/NADPH ratio is crucial for cyanobacterial cells. Since the production of PHB from glycogen provides ATP but consumes NADPH, the biopolymer could help the cells to regulate this ratio under conditions of electron excess [33].…”
Section: Physiological Function Of Phbmentioning
confidence: 99%
“…Recently, autotrophic sugar production and secretion have been engineered and demonstrated in cyanobacteria by various studies (Ducat et al, 2012;Lin et al, 2020;Thiel et al, 2019). An impressive proportion of the fixed carbon can be directed to sugar synthesis and exported from the cell.…”
Section: Resultsmentioning
confidence: 99%